The Tunka detector complex: from cosmic-ray to gamma-ray astronomy. (July 2015) - Budnev, N; Astapov, I; Barbashina, N; Bogdanov, A; Bogorodskii, D; Boreyko, V; Büker, M; Brückner, M; Chiavassa, A; Chvalaev, O; Gress, O; Gress, T; et al.
Abstract: TAIGA stands for "Tunka Advanced Instrument for cosmic ray physics and Gamma Astronomy" and is a project to build a complex, hybrid detector system for ground-based gamma- ray astronomy from a few TeV to several PeV, and for cosmic-ray studies from 100 TeV to 1 EeV. TAIGA will search for "PeVatrons" (ultra-high energy gamma-ray sources) and measure the composition and spectrum of cosmic rays in the knee region (100 TeV - 10 PeV) with good energy resolution and high statistics. TAIGA will include Tunka-HiSCORE (an array of wide-angle air Cherenkov stations), an array of Imaging Atmospheric Cherenkov Telescopes, an array of particle detectors, both on the surface and underground, and the TUNKA-133 air Cherenkov array.